Evaluation of the knowldege and practice of the third year student nurses about drugs by OSCE method - Roya Dokoohaki; Nasrin Sharifi; Shirin Rahnema; Parvin AzarHooshang; Iran Jahanbin (Iran University of Medical Sciences, 2008)
Background and Aim: One of the most important functions of nurses, which require preparation and powerful scientific background, skill in decision making and careful attention to drug laws is administration of the drugs to the patients. The aim of the present study was to evaluate the knowldege and practice of the student nurses about drugs by OSCE method at the end of the third year of their education.   Material and Method: In this cross- sectional study, 48 student nurses (45 females and 3 males), with a mean age of 21 years took part in a theoretical exam and 36 of them participated also in a practical exam. A demographic questionnaire including personal details, Over Time working (OT), the usage pharmacological sources and the level of encountering different pharmacological methods was used to collect data. Then, a theoretical exam, covering the whole drugs the subjects had learnt during 6 semesters, was taken and after that, 9 routes of drug administration (Suppository, NG tube, PO, SQ, IV, IM, ID, Topical and inhalation) were examined by OSCE Method in 2 consecutive days. The scores were given based on the drug administration check list.   Results: The findings showed that encountering students with different routes of drug administration were Topical =93.7%, Inhalation=31.25%, SUPP =43.75%, NG= 98%, ID=6.26%, SQ= 98%, IV = 100%, PO=100% and IM=100%.   The mean score of theoretical and practical exam were 49.02 and 63.8, respectively. A correlation of 0.32 was obtained between scores of theoretical and practical exam   Conclusion: Since drugs administration requires both pharmacological information and practical skills, special attention should be paid to the theoretical and practical education of student nurses.